Human capital factors and remuneration: analysis of relations, modelling of influence - Bilan, Yuriy; Mishchuk, Halyna; Dzhyhar, Tetiana (Business: Theory and Practice, 2017)
This paper argues that basing on existing theoretical studies of human capital factors fuzzy logic method shall be applied in in identifying their impact upon the interest on human capital use (wages). The suggested approach allows determining the factors impossible to describe through quantitative indicators, i.e. gender, education level, experience. Unlike traditional approaches, such as ranked assessments or investment cost indicators in the formation of certain human capital components, the use of the proposed methodology for analysing the link between human capital factors and remuneration allows applying real characteristics of the human capital of employees. Appropriate assessment can be the basis of modelling and correction of relations in determining wages and suitable decision-making regarding the development and changes in the structure of the human capital of the company.